Cloning, expression, and purification of the hemolysin/cytolysin (HlyE antigen) from Salmonella enterica serovar Typhi: Potential application for immunoassay development - Ong E.B.B.; Anthony A.A.; Ismail A.; Ismail A.; Lim T.S. (Elsevier Inc., 2024)
The hemolysin (HlyE) protein of Salmonella enterica serovar Typhi was reported to be antigenic. This work describes the cloning, expression, and purification of a hexahistidine-tagged HlyE protein under native conditions. Immunoblot analysis and a competitive enzyme-linked immunosorbent assay using sera from typhoid patients showed the presence of HlyE-specific antibodies in circulation. 2013 Elsevier Inc.